Cytotoxicity of Mahanimbine, Murryafoline A and S-Benzyldithiocarbazate on Human Leukemic Cell Line, CEM-SS - Kok, Yih Yih (2001)
Mahanimbine, a carbazole alkaloid was isolated from an ether extract of the stem bark of Murraya koenigii whilst Murrayafoline A was isolated from petroleum ether extract of the roots of Murraya koenigii. S-Benzyldithiocarbazate is a dithiocarbazic acid Schiff base derived from S-alkyl esters. They were found to exhibit cytotoxic activity against CEM-SS human T-lymphoblastic leukemic cells. The cytotoxic activity of Mahanimbine, Murrayafoline A and S-Benzyldithiocarbazate that inhibit 50 % growth (IC₅₀) of CEM-SS were 6 µg/ml, S µg/ml and 7.S µg/ml respectively. For comparative purposes, the IC₅₀ of several commercial cytotoxic drugs against CEM-SS were determined. The inhibition effect of Mahanimbine, Murrayafoline A and SBenzyldithiocarbazate were better than Methotrexate (IC₅₀ > 30 µg/ml), Doxorubicine (IC₅₀ = 21 µg/ml), Cytarabine (IC₅₀ > 30 µg/ml) and Colchecine (IC₅₀ = 8 µg/ml).These compounds were found to be less active than cis-diamine dichloroplatinwn and Vinorelbine tartrate with a IC₅₀ value of 3 µg/ml. In contrast, these three compounds were found to be less active against normal mouse fibroblasts cell, 3T3 with the IC₅₀ value of 11 µg/ml (Mahanimbine), 17 µg/ml (Murrayafoline A) and 10 µg/ml (SBenzyldithiocarbazate) respectively. The study showed that the proliferation of cells was inhibited before the cells were being killed. In addition, Mahanimbine, MurrayafolineA and S-Benzyldithiocarbazate caused programmed cell death by showing apoptotic features such as nucleus fragmentation, cell shrinkage, membrane blebbing and formation of apoptotic bodies. These were further confirmed with DNA laddering in agarose gel electrophoresis assay due to DNA fragmentation. DNA laddering was obtained after 24 hours of treatment by these three compounds in a doseindependent but time-dependent way. Mahanimbine and Murrayafoline A were shown to arrest CEM-SS cells at G1 phase of cell cycle using flowcytometry method. As a result, Mahanimbine, Murrayafoline A and S-Benzyldithiocarbazate were found as potent antitumor agents.